Pengaruh DOL dan DFL terhadap ROE pada Subsektor Makanan dan Minuman di BEI periode 2014-2019 - Annisa Nur Rahmah; Destian Arshad Darulmalshah Tamara; Rosma Pakpahan (Indonesian Journal of Economics and Management, 2021)
There was a theoretical mismatch between DOL and DFL against ROE in the Food and Beverage company in 2016, 2017, 2018 and 2019. This aim of this research to know the effect of DOL and DFL to ROE for Food and Beverages subsector which listed at IDX for 2014-2019 period. The research uses secondary data in form of a complete annual financial reports for 2013-2019 period which sourced from Indonesia Stock Exchange. Purposive sampling are using for research samples so used consist of 13 company. Panel data used in this research. The analysis method which suggested for the research is multiple regression model, adjusted determination coefficient, and hypothesis test. Based on hypothesis test, the use of DOL and DFL simultaneously did affecting the ROE significantly, meanwhile in partially, DOL negatively significant to ROE and DFL did not significantly affect ROE.